2019
DOI: 10.1055/a-0969-8623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Relative Drop Heights of Drop Jump Biomechanics in Male Volleyball Players

Abstract: Previous cross-sectional studies have reported that higher drop heights do not always result in improved performance, and may increase injury risk during drop jumps (DJ). The purpose of this study was to analyze the kinematics and kinetics during the DJ in order to determine the relative drop height that maximize performance without exposing the lower extremity joints to unnecessary loads. Twenty male Division I college volleyball players volunteered. Data were collected using 11 infrared cameras and two force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 44 publications
(89 reference statements)
3
27
1
Order By: Relevance
“…Volleyball players showed lower vertical GRF than the gymnastic and control groups, regardless of body weight. This supports previous findings which concluded that volleyball players seem to be able to absorb an impact force between 1.9 to 4.0 times their body weight [ 31 , 39 , 40 ]. These results might be related to lower limb movement, wherein a negative correlation between knee flexion and the magnitude of the peak GRF is found [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Volleyball players showed lower vertical GRF than the gymnastic and control groups, regardless of body weight. This supports previous findings which concluded that volleyball players seem to be able to absorb an impact force between 1.9 to 4.0 times their body weight [ 31 , 39 , 40 ]. These results might be related to lower limb movement, wherein a negative correlation between knee flexion and the magnitude of the peak GRF is found [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…This could be also due to the nature of volleyball wherein, rather than gymnastics during landing, volleyball players must control their GRF quickly in order to react to any other unexpected stimuli incoming from the game [ 43 ]. Even though a study in volleyball suggested that impact force attenuation depended on the height of the drop [ 39 ], these results indicate that volleyball players have fewer lower limb injuries because the game seems to be associated with strategies of impact force attenuation.…”
Section: Discussionmentioning
confidence: 90%
“…The DJH time × protocol interaction was significant (p = 0.022; η 2 = 0.171; statistical power = 0.781). Simple main effects showed significant improvements in DJH after FRE at POST2 when compared with The formula: 1 8 gT 2 (g = 9.81 m/s −2 ; T = t 4 − t 3 ) was used to calculate drop jump height (DJH) [25,26]. The mechanical power of the hip, knee, and ankle joints was calculated by inverse dynamics and normalized by body weight.…”
Section: Resultsmentioning
confidence: 99%
“…The instant of the first and second foot contact (t1 and t4) and take-off of the foot from the force platforms (t3) was determined by assessing the 30 Newton vertical ground reaction force threshold. The formula: gT 2 (g = 9.81 m/s -2 ; T = t4 − t3) was used to calculate drop jump height (DJH) [25,26]. The mechanical power of the hip, knee, and ankle joints was calculated by inverse dynamics and normalized by body weight.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation